2003
DOI: 10.1128/jcm.41.8.3719-3728.2003
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Approach to Identification of Mycobacterium bovis Diagnostic Antigens in Cattle

Abstract: Differential delayed-type hypersensitivity skin testing with tuberculin purified protein derivatives from Mycobacterium bovis and M. avium is the standard for diagnosing bovine tuberculosis. However, improved tests based on defined, specific antigens are urgently needed. In the present study, a combination of bioinformatics, molecular biology, and bovine models of infection were used to screen mycobacterial proteins for their potential as diagnostic reagents which could be used in a whole-blood assay for diagn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
44
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 44 publications
0
44
0
4
Order By: Relevance
“…The diagnostic antigen selected should ideally accommodate the possible application of the M. bovis bacillus CalmetteGuérin (BCG) vaccine in the future (9). Genetic comparison of M. bovis and a number of BCG strains has revealed several large genomic regions in BCG strains that have been lost during the attenuation process (5,18); and because of their theoretical lack of interference with a BCG vaccine, the proteins encoded by these regions have received growing attention as diagnostic antigens, especially antigens from region of difference (RD) RD1 (1,10,19,26,30). All studies have clearly identified the two RD1 antigens ESAT6 and CFP10 as being the most immune dominant of those tested with experimentally infected cattle.…”
mentioning
confidence: 99%
“…The diagnostic antigen selected should ideally accommodate the possible application of the M. bovis bacillus CalmetteGuérin (BCG) vaccine in the future (9). Genetic comparison of M. bovis and a number of BCG strains has revealed several large genomic regions in BCG strains that have been lost during the attenuation process (5,18); and because of their theoretical lack of interference with a BCG vaccine, the proteins encoded by these regions have received growing attention as diagnostic antigens, especially antigens from region of difference (RD) RD1 (1,10,19,26,30). All studies have clearly identified the two RD1 antigens ESAT6 and CFP10 as being the most immune dominant of those tested with experimentally infected cattle.…”
mentioning
confidence: 99%
“…A kit based on whole-blood production of IFN-␥ detected by enzyme-linked immunosorbent assay (ELISA) is available and has the advantage of relative simplicity, but being based on PPD, it does not ameliorate the poor specificity of skin testing (6). In addition, this test requires 10 ml of blood, a large amount if one considers its application in pediatric practice.We were interested to determine, by the use of a sensitive IFN-␥ ELISA, whether a form of the whole blood stimulation assay that is used by many groups to assay antigen specific responses to RD1 encoded antigens (1,3,7,9,16) could match the performance of the ELISPOT assay. Ethical permission for this study was provided by the Harrow local research ethics committee (Harrow LREC 1646).…”
mentioning
confidence: 99%
“…We were interested to determine, by the use of a sensitive IFN-␥ ELISA, whether a form of the whole blood stimulation assay that is used by many groups to assay antigen specific responses to RD1 encoded antigens (1,3,7,9,16) could match the performance of the ELISPOT assay. Ethical permission for this study was provided by the Harrow local research ethics committee (Harrow LREC 1646).…”
mentioning
confidence: 99%
“…We applied a high-throughput immunological screening system based on pools of chemically synthesized peptides representing the complete amino acid sequences of target proteins. In the first set of experiments we assessed the immunogenicity of the 28 potential antigens encoded in the RD1, RD2, and RD14 gene regions that are deleted from the genome of BCG Pasteur (Brosch et al, 2007;Garnier et al, 2003) Other immunogenic antigens identified that could be useful for either diagnosis or as vaccine antigens include proteins belonging to the important ESAT-6 protein family (Pallen, 2002), such as Rv3019c or Rv0288 (Aagaard et al, 2003;Cockle et al, 2006;Vordermeier et al, 2003).…”
Section: Comparative Genomicsmentioning
confidence: 99%